The COVID-19 U’Z generation or the pandemial university students : Characterization and cases study - Miquel-Vergés, Joan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The purpose of this work is to characterize, from different points of view, the human group of university students that was affected by the COVID-19 pandemic. First of all, we will look for what distinctive features they share, and we will try to assign them a name, letters and/or distinctive labels. And, secondly, we will analyze the possibility to classify them as a “generation”, with all that this implies. To do this, however, we must first establish what we understand by “generation”.